Relapsing polychondritis - Miyasaka, Lincoln Sakiara; Andrade Junior, Ary de; Bueno, Carlos Eduardo; Atallah, Alvaro Nagib (São Paulo Medical Journal, 1998)
PURPOSE: This article describes a clinically-diagnosed case of relapsing polychondritis (RP), attended at the Hospital São Paulo, and presents a literature review of the subject. SOURCE OF RESEARCH: The literature review was made via Medline (1990-96), Lilacs (1980-96), textbooks of rheumatology, and some articles about the history of the disease. In Medline, 113 articles from 1990 to 1996 were found, and there were 23 articles from 1980 to 1996 in Lilacs. RESEARCH PROCEDURE: We reviewed the articles available at BIREME (Biblioteca Regional de Medicina) with the primary focus being on the disease in question. SUMMARY: RP is a rare disease of unknown etiology described initially by Jackson-Wartenhorst in 1923 and characterized by a recurrent and acute inflammatory process that causes the collapse of the cartilaginous structures and their subsequent replacement by fibrous connective tissue. The cartilage most commonly attacked is that of the auricle of the ear and nasal septum, while the cartilage of the trachea, larynx, epiglottis, ribs, and articulations may also be involved. Ocular inflammations and systemic reactions with fever are also described. In 1976, McAdam presented a complete prospective study of 23 patients, reviewed the 136 cases described up until that time, and then proposed diagnostic criteria which were later expanded by Damiani and Levine. Currently, more than 500 cases have been described. CONCLUSION: Although a rare disease, better knowledge of it is needed, as RP may be lethal with tracheal collapse and obstruction of respiratory pathways, making precise diagnosis and adequate therapeutic intervention necessary.